Предмет:
МатематикаАвтор:
hunterf47fАвтор:
poncioloveАвтор:
trey437Автор:
janaeАвтор:
bartonАвтор:
sethe^4-10e^2+1=0
замена e^2=t >=0
t^2 - 10 t + 1 =0
D=b^2-4ac = 100 - 4 = 96
t12 = (10 +- √96)/2 = (10+-4√6)/2 = 5 +- 2√6
2√6 < 5 значит оба корня подходят
1. e^2=5 + 2√6
e₁₂ = +-√(5 + 2√6)
2. e^2 = 5 - 2√6
e₃₄ = +-√(5 - 2√6)
Автор:
schaeferДобавить свой ответ
Предмет:
МатематикаАвтор:
zion8ptuОтветов:
Смотреть
Предмет:
Русский языкАвтор:
lucanodouglasОтветов:
Смотреть
Предмет:
Русский языкАвтор:
adrianОтветов:
Смотреть